Controversies in aortic dissection and aneurysmal disease - Pagano, Domenico; Haverich, Axel; Mascaro, Jorge; Bonser, Robert S. (Springer London, 2014)
This book reviews the surgical management of patients with aortic disease, revealing many options open to cardiovascular specialists in this often controversial area of management. It reviews each controversy and provides clinical information for cardiac surgery, and discusses the spectrum of disorders and their management.   With the knowledge base in this discipline changing rapidly, Controversies in Aortic Dissection and Aneurysmal Disease meets an important requirement to consolidate the wide-ranging information on which clinicians must base their practice. It is directed towards surgeons, physicians, and healthcare workers involved in the care of patients requiring cardiac, cardiothoracic and cardiovascular surgery. This book will be an essential resource for these professionals looking to accelerate the translation of basic research findings into clinical study and practice.